The impact of climate change induced extreme weather events on microbial dynamics and public health: an in-depth review on water quality and ecosystem resilience - Huang, Shangshu; Jiang, Fahui; Dong, Qi; Yu, Junfeng; Fan, Ke; Wang, Zhijian; Hao, Shouli; Qiao, Yanjun (Frontiers in Environmental Science, 2025)
Climate change is significantly increasing the frequency and intensity of extreme weather events (EWEs), including severe storms, catastrophic floods, prolonged heatwaves, and extended droughts. These events have significant impacts on hydrological systems, microbial ecosystems, and public health. Therefore, this detailed review was carried out to explore the impact of climate change induced extreme weather events on microbial contamination and public health. The detailed search revealed that EWEs can lead to increased microbial contamination in water sources, potentially causing outbreaks of waterborne diseases. In addition, EWE can also disrupt nutrient cycles and alter microbial community structures, affecting ecosystem stability and resilience. Moreover, EWEs can mobilize pollutants such as microplastics, antibiotic-resistant genes, and PFAS, further degrading water quality. Despite these challenges, microbial communities can play a crucial role in mitigating the impacts of EWEs by degrading pollutants and stabilizing nutrient cycles. In addition, we found that real-time monitoring techniques, such as environmental DNA (eDNA) profiling, can help identify contamination sources and inform targeted interventions. At last, we observed that integrating microbial insights into ecosystem management and public health strategies is essential for developing resilient and adaptive approaches to address the escalating impacts of climate change on water quality and public health. Therefore, this study is particularly important in highlighting its contribution to the development of more effective and resilient management practices in the face of increasing climate variability.